PENGEMBANGAN ALAT OLAHRAGA KURSI RODA BALAP BAGI ANAK TUNADAKSA BERBASIS ERGONOMI DAN ANTROPHOMETRI - Gandes Luwes, Ulwa Humairok; Himawanto, Dwi Aries; Widyastono, Herry (Universitas Pendidikan Ganesha, 2021)
The purpose of the research: to develop a racing wheelchair for wheelchair racing activities for children with disabilities based on local anthropometry and ergonomics. This research is an RnD research, namely the development of media or sports equipment for children with physical disabilities. The research method used is the ADDIE method. The subjects of this study were two children with physical disabilities in SLB YPAC Surakarta. Data collection is obtained from library books, then looking for supporting paper data. After that, the data collected is analyzed, designing the development of a racing wheelchair, implementing and evaluating so that a conclusion can be drawn. Secondary data were obtained from literature books that underlie special education technology for children. Primary data is obtained from papers or journals on official websites on the internet. The data that has been collected is compiled and then analyzed, to obtain an appropriate conclusion. The results showed that children with physical disabilities need a racing wheelchair by the specifications of their needs, with high quality and affordable prices. Expert validators, practitioners, and users respond positively to the model developed through aspects of attractiveness, motivation, and convenience. The racing wheelchair design that has been developed is effective as a sporting tool for racing wheelchairs based on ergonomics and anthropometry through aspects of media convenience, display of media results and technical quality, the effectiveness of sports equipment. Conclusion: Children with physical impairment in doing sports activities need anthropometric and ergonomic local-based racing wheelchair technology.